Preparation, Characterization and NO-CO Redox Reaction Studies over Palladium and Rhodium Oxides Supported on Manganese Dioxide - M. S. Fal Desai; R. K. Kunkalekar; A. V. Salker (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The catalytic activity of PdO/MnO2 and Rh2O3/MnO2 is investigated for NO-CO redox reaction. Supported catalysts are prepared by wet impregnation method. Among the tested catalysts, PdO/MnO2 shows higher activity for this reaction. Active metal dispersion on MnO2 enhances the selectivity for N2 over N2O in this reaction. The XRD substantiate the formation of MnO2 monophasic phase. SEM images show the formation of elongated particles. TEM images indicate nano-size rod-like morphologies. An increase in the catalytic activity is observed on supported Pd and Rh oxides on MnO2. Temperature programed desorption studies with NO and CO are undertaken to investigate the catalytic surface studies. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)